A management program for preventing occupational blood-borne infectious exposure among operating room nurses: an application of the PRECEDE-PROCEED model. Issue 1 (January 2020) - Lin, Hua; Wang, Xiaoyan; Luo, Xiaohui; Qin, Zhen
Objectives: The study aim was to determine the effect of an occupational blood-borne pathogen exposure (OBE) management program based on the PRECEDE-PROCEED model on knowledge, attitude and behaviour regarding OBE prevention among operating room nurses. Methods: This was a one-group pre-test post-test experimental study. The PRECEDE-PROCEED model was used to design and evaluate the effect of an OBE management program on 87 operating room nurses from February to July 2018. The study included pre-intervention assessment; risk factor analysis; interventions targeted to predisposing, reinforcing and enabling factors and focusing on areas of low scoring; and a post-intervention assessment. Attitudes, knowledge and behaviour compliance regarding OBE were measured before and after the 6-month program using a self-developed questionnaire. Descriptive epidemiological analysis and t-tests were used for data analysis. Results: Low-scoring items for OBE knowledge, attitudes and behaviour were identified in the baseline assessment. Six months post-intervention, there were significant improvements in attitudes toward OBE prevention, in knowledge about OBE safety precautions and in behaviour compliance with standard precautions. Conclusions: The findings indicate the effectiveness of an OBE management program based on the PRECEDE-PROCEED model for improving knowledge, attitudes and behaviour adherence to OBE prevention among operating room nurses.